Sultan Kozhakhmetov And Development of Didactics in His Pedagogical Heritage (Journal of Educational Sciences, 2016)
In the article «Sultan Kozhakhmetov and development of didactics in his pedagogical heritage» is characterized by way of formation S. Кozhakhmetov as a researcher - didactic. Disclosed his works on the following directions: «Questions of General pedagogy and pedagogic», «Technology of training and subjects of the learning process», «History of педагогик». Analyzed the contribution S. Кожахметова in the development of pedagogical knowledge of didactic principles on the demands of the today’s practice.
Keywords: didactics; researcher - didactic; the subjects of the training process